GENESIS OF THE CONCEPT OF SUSTAINABLE DEVELOPMENT AND THE DIRECTIONS OF ITS ACHIEVEMENT IN SOCIETY - Rudevskaya, Victoria; Shvets, Natalia; Shkvaryliuk, Marta; Tanase, Victoria (Socio-economic relations in the digital society, 2022)
To protect the environment and prevent the growth of social and environmental risks, the concept of sustainable development has been shaped. This means meeting the needs of people today without harming the environment or creating other problems in the future. The concept of sustainability is constantly changing, and different people will have different ideas about how best to implement it. In the article, with the help of modern methods of scientific knowledge, an analysis of theoretical approaches to the interpretation of sustainable development is carried out. The relevance of theoretical and methodological studies of the concept of sustainable development as the basis for the development of modern society is substantiated. Based on methodological generalizations, the principles of the concept of sustainable development have been clarified. Based on the basis of the study of the modern understanding of the essence of the concept, the directions for achieving the goals of sustainable development of society are highlighted, and approaches to assessing the sustainable development of socio-economic systems are identified. The article analyzes the dynamics of the world sustainable development index and establishes its growing trend over the past decade and the recession during the global crisis caused by the pandemic. The presented analytical data indicate the intensification of the transition of countries to sustainable development, and this activity is much higher in low-income countries compared to high-income countries. The article substantiates the conclusion about the need to form an appropriate investment potential to ensure the sustainable development of society, which requires a strategic approach that would be based on changing the entire philosophy of thinking and political activity.